A Novel Long Noncoding RNA, lncR-125b, Promotes the Differentiation of Goat Skeletal Muscle Satellite Cells by Sponging miR-125b - Zhan, Siyuan; Qin, Chenyu; Li, DanDan; Zhao, Wei; Nie, Lu; Cao, Jiaxue; Guo, Jiazhong; Zhong, Tao; Wang, Linjie; Li, Li; Zhang, Hongping (Frontiers in Genetics, 2019)
Long noncoding RNAs (lncRNAs) have emerged as essential regulators of skeletal myogenesis, but few myogenesis-associated lncRNAs have been identified and our understanding of their regulatory mechanisms remains limited, particularly in goat. Here, we identified a novel lncRNA, TCONS_00006810 (named lncR-125b), from our previous lncRNA sequencing data on fetal (45, 60, and 105 days of gestation, three biological replicates for each point) and postnatal (3 days after birth, n=3) goat skeletal muscle, and found that it is highly expressed in skeletal muscle and gradually upregulated during skeletal muscle satellite cell (SMSC) differentiation in goat. Notably, overexpression of lncR-125b accelerated the expression of myogenic differentiation 1 (MyoD 1) and myogenin (MyoG), and the formation of myotubes, and knockdown of lncR-125b showed opposite effects in SMSCs. Results of dual-luciferase assay and quantitative real-time polymerase chain reaction revealed that lncR-125b acts as a molecular sponge for miR-125b and that insulin-like growth factor 2 (IGF2), a critical regulator of skeletal myogenesis, is a direct target gene of miR-125b. Further analyses showed that lncR-125b negatively regulates miR-125b expression and positively regulates IGF2 expression in SMSCs. Mechanistically, lncR-125b promotes SMSC differentiation by functioning as a competing endogenous RNA (ceRNA) for miR-125b to control IGF2 expression. These findings identify lncR-125b as a novel noncoding regulator of muscle cell differentiation and skeletal muscle development in goat.